A Sport Injury Poster: Alpine Skiing - Bronder, Lucas; Savage, Maya; Sempala, Randi; Milligan, Anna-Marie (MacEwan University Student eJournal, 2020)
Skiing is an exciting winter sport; however, it isdefined as a high-risk sport for significantinjuries. Among upper body and lowerbody injuries, common traumas to the body indownhill skiers are sprains of the ulnar collateralligament (UCL), which is part of the thumb joint,and tibia fractures.The analysis and research will outline thefollowing of each injury:• Mechanism of injury• Treatment• Rehabilitation• Prevention